Immediate effect of short duration of slow deep breathing on heart rate and blood pressure in healthy young adults - Bhavna; Ritu Adhana; Jay Ballabh Kumar; Anjali Verma; Jaspreet Kaur; Sanket Jheetey; Arun Kumar (International Journal of Health and Clinical Research, 2021)
Background: Pranayama is an ancient technique involving rhythmic and slow breathing. It is proven that regular practice of pranayama decreases sympathetic activity, increases parasympathetic tone, improves physical and mental health, decreases the effect of strain and stress on the body and improves respiratory and cardiovascular functions.Methods: Heart rate and blood pressure of the subjects (n=140, age=18-25 years) was recorded following standard procedure. First, subject had to sit comfortably. The subject is directed to inhale through both nostrils slowly up to maximum for about 5 seconds and then exhale slowly up to maximum through both nostrils for about 5 seconds. These steps complete one cycle of slow deep breathing (respiratory rate 6/min).After 5 minutes of this breathing practice, both the parameters were recorded again.Results: It was noted that after slow deep breathing (respiratory rate 6/min) for 5 minutes, heart rate and blood pressure decreased.Conclusion: This study suggested that practicing of slow deep breathing (respiratory rate 6/minute) for 5 minutes could improve autonomic nervous system imbalance towards parasympathetic dominance.